VALUE ADDED TAX ON CONSIGNMENT POST- OMNIBUS LAW - Suparna Wijaya; Anni Khoiriyah Sinaga (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Abstract This study aims to determine the treatment of consignment in accounting according to PSAK; the difference in the imposition of VAT on consignment before and after the omnibus law; and the advantages and disadvantages of changing the policy of imposing VAT on consignment after the omnibus law. This study uses a qualitative method with a literature study approach and interviews. Interviews were conducted online through forms and video conferences to five interviewees consisting of lecturers specialized in accounting and taxation of the Polytechnic of State Finance STAN. From this study it was concluded that the revision of PSAK 23 to PSAK 72 did not cause changes to the accounting method of recording consignment transactions. With regard to the imposition of VAT, the differences between UU PPN 1984 and UU Cipta Kerja include the time that tax is owed, crediting input taxes, issuing tax invoices, notes on returns, and replacement tax invoices. The advantages and disadvantages of this rule change can be viewed from the side of administration, supervision, tax credit mechanism, and equalization of VAT and Income Tax.